Characterization of the Zebrafish Cell Landscape at Single-Cell Resolution - Jiang, Mengmeng; Xiao, Yanyu; E, Weigao; Ma, Lifeng; Wang, Jingjing; Chen, Haide; Gao, Ce; Liao, Yuan; Guo, Qile; Peng, Jinrong; Han, Xiaoping; Guo, Guoji (Frontiers in Cell and Developmental Biology, 2021)
Zebrafish have been found to be the premier model organism in biological and regeneration research. However, the comprehensive cell compositions and molecular dynamics during tissue regeneration in zebrafish remain poorly understood. Here, we utilized Microwell-seq to analyze more than 250,000 single cells covering major zebrafish cell types and constructed a systematic zebrafish cell landscape. We revealed single-cell compositions for 18 zebrafish tissue types covering both embryo and adult stages. Single-cell mapping of caudal fin regeneration revealed a unique characteristic of blastema population and key genetic regulation involved in zebrafish tissue repair. Overall, our single-cell datasets demonstrate the utility of zebrafish cell landscape resources in various fields of biological research.